Discontinuation of first-line bevacizumab in metastatic colorectal cancer: the BEAWARE Italian Observational Study. Issue 3 (June 2019) - Lonardi, Sara; Nasti, Guglielmo; Fagnani, Daniele; Gemma, Donatello; Ciuffreda, Libero; Granetto, Cristina; Lucchesi, Sara; Ballestrero, Alberto; Biglietto, Maria; Proserpio, Ilaria; Bergamo, Francesca; Proietti, Emanuela; et al.
Aims: BEAWARE investigated the pattern of first-line bevacizumab early interruption in the Italian real-world setting of metastatic colorectal cancer. Methods: A total of 386 patients were followed for 15 months after first-line chemotherapy + bevacizumab start. The rate of bevacizumab interruption for progression or adverse drug reactions (ADRs) constituted the primary endpoint. Results: A total of 78.2% of patients interrupted bevacizumab: 56.6% for progression, 7.3% for ADRs, and 36.1% for other reasons. Median treatment duration was 6.7, 2.5, and 4.6 months, respectively. Median progression-free survival was 10.3 months; however, 35.8% of patients were not progressed and were thus censored at the data cutoff of 15 months, while 21.8% were still receiving bevacizumab. Patients discontinuing for progression/ADRs more frequently had metastases in >1 site ( p = .0001), and a shorter median progression-free survival (6.9 vs 13.9 months, p < .0001). Conclusions: In Italy, first-line bevacizumab is interrupted mainly for progression, only 7.3% due to adverse events, and about one third of cases for other reasons. In clinical practice, the attitude to treat until progression as per guidelines might be implemented. ClinicalTrials.gov Identifier: NCT01609075